2010
DOI: 10.1212/wnl.0b013e3181cbcdc4
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CSF N -acetylaspartylglutamate in patients with free sialic acid storage diseases

Abstract: Objective: To investigate body fluids of patients with undiagnosed leukodystrophies using in vitro 1 H-NMR spectroscopy (H-NMRS). Methods:We conducted a cross-sectional study using high-resolution in vitro H-NMRS on CSF and urine samples. Results:We found a significant increase of free sialic acid in CSF or urine in 6 of 41 patients presenting with hypomyelination of unknown etiology. Molecular genetic testing revealed pathogenic mutations in the SLC17A5 gene in all 6 patients. H-NMRS revealed an increase of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 10 publications
3
16
0
Order By: Relevance
“…It was almost undetectable in the neocortex and the cerebellar cortex, but reached high expression levels in different nuclei of the midbrain and brain stem, as well as deep cerebellar nuclei and the spinal cord. Thus, NAAGS-II is expressed in those areas with high NAAG concentrations (1,18,20,35). NAAGS-I may be responsible for the overall basal NAAG synthesis, whereas NAAGS-II evolved to ensure high NAAG levels in the caudal brain regions and spinal cord.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was almost undetectable in the neocortex and the cerebellar cortex, but reached high expression levels in different nuclei of the midbrain and brain stem, as well as deep cerebellar nuclei and the spinal cord. Thus, NAAGS-II is expressed in those areas with high NAAG concentrations (1,18,20,35). NAAGS-I may be responsible for the overall basal NAAG synthesis, whereas NAAGS-II evolved to ensure high NAAG levels in the caudal brain regions and spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated NAAG concentrations have been found in the cerebrospinal fluid of Pelizaeus-Merzbacher disease patients (39,40), and the Pelizaeus-Merzbacher disease-like disease caused by mutations in the connexin 47 gene (41), sialic acid storage diseases (35), and a leukodystrophy with an unknown genetic cause (22). Slightly elevated NAAG levels in cerebrospinal fluid also occur in Canavan disease (39,40), which is caused by deficiency in the NAA degrading enzyme aspartoacylase (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase of NAAG was also observed in the CSF of one patient with Canavan disease [3], one PMLD patient harboring a homozygous deletion in the GJC2 gene [4] and two patients with a severe hypomyelination pattern of unknown cause [5]. In addition, we recently reported that CSF NAAG was increased in 6 patients with sialic acid storage disease (SASD) associated with mutations[6]. …”
Section: Introductionmentioning
confidence: 99%
“…SLC17A5-related conditions include infantile sialic acid storage disease (ISSD; OMIM #269920, a lethal multisystem disorder), Salla disease (OMIM #604369, a slowly progressive, predominantly neurological condition), and intermediate phenotypes (Aula et al 2000;Verheijen et al 1999). Recently, SLC17A5 mutations have also been identified in children and adults with cerebral palsy-like chronic encephalopathy; thus, the recognized spectrum of clinical phenotypes continues to expand (Debray et al 2011;Mochel et al 2009Mochel et al , 2010. ISSD is situated at the opposite (severe) end of the SLC17A5 disease spectrum; cardinal features include profound developmental delay, failure to thrive, hepatosplenomegaly, coarse facies, hypopigmentation, and (typically) death in infancy (Lemyre et al 1999).…”
Section: Introductionmentioning
confidence: 99%